Lipid Profile in Female Patients with Rheumatoid Arthritis - Berrin Gündüz; Belgin Erhan; Seçil Hıncal Boriçi; Ayşe Nur Bardak; Zeynep Kılıç; Bora Akyürek (Archives of Rheumatology, 2007)
Objective: To investigate the lipid profile in patients with rheumatoid athritis Patients and Methods: The levels of total serum cholesterol, triglycerides, high density lipoprotein cholesterol (HDL-chol), low density lipoprotein cholesterol (LDL-chol), sedimentation, C reactive protein (CRP) and rheumatoid factor (RF) in 40 postmenopausal female patients diagnosed as Rheumatoid Arthritis according to ACR criteria were compared with 40 postmenopausal healthy women at the same age group. Results: The mean age, menopausal status and body mass index were similar in both groups (p>0.05). In RA group, the levels of erythrocyte sedimentation rate and CRP were significantly higher than the control group (p=0.005, p=0.041 respectively). Levels of total cholesterol, triglycerides, LDL-chol levels did not show a significant difference between the groups (p>0.05). Serum HDL-chol levels were higher in RA patients but this difference was not significant (p=0.059). Conclusion: According to this study no significant difference was found in lipid levels between the RA patients and control group. (Rheumatism 2007; 22: 88-90)